A New Chemical Probe Challenges the Broad Cancer Essentiality of CK2. (May 2021) - Licciardello, Marco P.; Workman, Paul
Abstract : Casein kinase 2 (CK2) is highly expressed in cancer and has been considered a potential therapeutic target. Wells and colleagues developed and characterized the new CK2 inhibitor SGC-CK2-1. Unexpectedly, this potent and highly selective chemical probe does not show broad antiproliferative activity in cancer cells.